2019
DOI: 10.3390/f10070591
|View full text |Cite
|
Sign up to set email alerts
|

Super Absorbent Polymers Buried within Dry Soil Attract Formosan Subterranean Termites (Blattodea: Rhinotermitidae)

Abstract: Baiting is one of the main methods to control subterranean termites. Many previous studies showed that subterranean termites avoid making tunnels within dry soil and feeding on dry wood, which may decrease bait infestation and consumption in drought areas. Super absorbent polymers are a group of materials that can retain large amounts of water and improve the moisture content of soil and bait matrices, and therefore may attract termites. In the present study, choice tests were conducted in the laboratory to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Although these water-retaining materials increased bait consumption, they did not cause significant aggregation by termites, probably because super absorbent polymers are gel-like and therefore termites cannot make tunnels to access the bait matrices (Xie et al, 2019a(Xie et al, , 2019b. The present study showed that bentonite filled in the baiting containers not only caused aggregation of termites but also increased wood consumption under low-moisture conditions (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Although these water-retaining materials increased bait consumption, they did not cause significant aggregation by termites, probably because super absorbent polymers are gel-like and therefore termites cannot make tunnels to access the bait matrices (Xie et al, 2019a(Xie et al, , 2019b. The present study showed that bentonite filled in the baiting containers not only caused aggregation of termites but also increased wood consumption under low-moisture conditions (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…This could result from the fact that several farmers in the study area practice the destruction of epigeal nesters in maize fields (Loko et al, 2019a). In addition, it is known that subterranean termites adapt better in cultivated land because they can migrate in depth during harsh conditions such as drought (Xie et al, 2019). They great abundance of A. evuncifer in maize fields in all agro-ecological zones could be explained by the polyphagia of this species, which is able to feed on different subtracts (Ogedegbe and Eloka, 2015), and its adaptation in different environments (Wekhe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies tried to create a microhabitat more suitable for termites by adding super absorbent polymers into bait stations. Although these water-retaining materials increased bait consumption, they did not cause significant aggregation by termites, probably because super absorbent polymers are gel-like and therefore termites cannot make tunnels to access the bait matrices ( Xie et al, 2019a ; Xie et al, 2019b ). The present study showed that bentonite filled in the baiting containers not only caused aggregation of termites but also increased wood consumption under low-moisture conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%